Religious-Heritage Tourism Development Strategies in Balun Village, East Java - Retnowati Wiranto; Masroer Ch. Jb. (Transformatif, 2023)
Religious tolerance (between Islam, Christian, Hindu) and multiculturalism is a special value in Balun Village, East Java. Religious inclusiveness does not only occur at the social life, but down to the family level. In Balun family, it is normal to have interfaith marriage. By using in-depth interviews and involved observations, this research is able to reveal that the tolerance value derives from the characteristics of rural communities that tend to place religion as a social religion. The sacredness of religion adapt with the existing traditions that is still be the most important control, rather than religion. The history of religious heterogeneity in Balun also gives an important role to the harmony. This research attempts to explain the potentials and challenges to develop multi-religious tourism and describe the appropriate strategy. A living lab approach that focusing attention to the user identified to be the best. In the living lab, experts and academics role to be the brokers and systems designers, stakeholders and potential local communities are regulators and executors, and the public directly involving in the development project as the evaluators. By utilizing social media, the development of a multi-religious tourism in Balun is possible action in the midst of the pandemic. Providing a platform or website as an alternative solution for virtual tourism is a genious offer for the development of Sustainable Development Goals (SDGs).